Owner capabilities in project organizing: Managing disruptions on infrastructure projects - Dinesh Shenoy; Biswajit Mahanty (Project Leadership and Society)
Megaprojects are large-scale, complex initiatives that often encounter major disruptions during their life cycle. These disruptions have the potential to seriously impair the viability of the megaprojects. They may also cause severe damage to the economy in the region where they are emerging. To overcome disruptions, and to enhance their delivery performance, the strategic management concept of dynamic capabilities is being increasingly applied. In the context of megaproject owners, there is a need to understand what capabilities are required and how they are developed in the face of disruptions.Drawing upon longitudinal data over a period spanning 50 years for three megaprojects in the urban development (metro rail) domain, this study examines key disruptions that may influence the development of owner capabilities. Specifically, this study identifies four project capabilities: i) a strategic capability to continuously engage with, and manage external stakeholders, ii) a strategic capability to preserve value and transform the delivery process, iii) a governance capability to enhance organizational resilience, and iv) a commercial capability to manage knowledge and partnerships. Given that disruptions are repetitive in nature, owners would need these project capabilities to overcome disruptions.